Associação da aptidão física de idosos saudáveis com o desempenho na tarefa de levantar-se do solo. - Costa, João Vitor Leme da; Cattuzzo, Maria Teresa; Santos de Santana, Frederico; Feng Yu Hua; Safons, Marisete Peralta (Fisioterapia Brasil, 2018)
The objective of this cross-sectional study was to examine the association of physical fitness with performance in the task of getting up from the floor in healthy elderly individuals. Fifty-six volunteers (71.8 ± 6.96 years, 68.8 ± 14.02 kg, 1.60 ± 0.97 cm) were classified according to the body mass index. Physical fitness assessment was performed using the following functional tests: Timed Up and Go; Unipodal support test; Sit and reach test and Sit and stand test. The time and number of attempts for the task of getting off the ground were checked using the Kinovea Software. To verify the association between the variables, the Spearman correlation test was used. The level of significance was set at p <0.05. The results showed that there was an association between the performance in the task of getting up from the ground with BMI (p <0.009), dynamic balance / mobility (p <0.001) and lower limb muscle strength (p <0.001). Thus, it is plausible to admit that the task of getting up from the floor proved to be a summary measure of physical health in the sample studied.